IMPROVING THE EIGHTH-GRADE STUDENTS’ READING COMPREHENSION AT SMP MUHAMMADIYAH 1 DENPASAR THROUGH NUMBERED HEAD TOGETHER (NHT) - Inayah Alfin Fahira; Anak Agung Istri Yudhi Pramawati; Ida Bagus Nyoman Mantra (Academic Journal on English Studies (AJOES), 2023)
Reading a book is like letting the world in. Good reading comprehension can help students, in particular, expand their thinking and creativity, which will improve their learning outcomes. Preliminary research indicates that the majority of class VIII D students at SMP Muhammadiyah 1 Denpasar for the 2022–2023 academic year struggle with reading comprehension. It was challenging for them to comprehend word meanings, identify phrase meanings, recognize specific information, and so on. Therefore, the purpose of the study was to determine whether the Numbered Heads Together method can enhance the reading comprehension of class VIII students at SMP Muhammadiyah 1 Denpasar. The researcher carried out classroom action research to meet these objectives. To gather the necessary data, research tools in the form of exams and questionnaires were made available. The data were then examined by comparing the pre-test and post-test findings, which revealed a considerable improvement in the respondents' average score from the pre-test to the post-test. According to the data, the participants' average pre-test score was 50.83, their post-test I score was 66, and their post-test II score was 74.83. As additional evidence, a survey was administered at the conclusion of the previous cycle, and the findings revealed that the Numbered Heads Together technique had been successfully applied. Based on the study's findings, it can be said that using the Numbered Heads Together method will help class VIII students at SMP Muhammadiyah 1 Denpasar read more fluently throughout the 2022–2023 academic year.